Enhancing Real-World Physics Problem-Solving Skills through Mind Map-Based Scaffolding: The Role of Metacomponents among Pre-University Students - Siti Nazirah Butai; Fatin Aliah Phang; Erni Yulianti (ASEAN Journal of Educational Research and Technology, 2027)
Physics problem-solving is essential in physics education, yet many pre-university students struggle to apply concepts to real-world contexts. This study examines the effectiveness of integrating mind map-based scaffolding with metacomponents to enhance real-world physics problem-solving skills (RWPPS). A quasi-experimental pre-test–post-test non-equivalent group design involved 253 students at Universiti Malaysia Sabah. The experimental group used mind maps to define problems, organize information, and plan strategies with guided scaffolding, while the control group received conventional lectures. Data from open-ended RWPPS assessments showed that the experimental group significantly outperformed the control group, with improvements across all metacomponent sub-skills, especially monitoring. Normalized gain results indicated higher learning gains in the experimental group, highlighting the approach’s effectiveness in fostering structured and reflective problem-solving.